PENINGKATAN KETERAMPILAN MENULIS CERITA PENDEK DENGAN COOPERATIVE LEARING METHODS PADA SISWA KELAS XI IPA 1 SMAN 3 METRO - Wiwik Dwi Koryati (LPPM STKIP PGRI Bandar Lampung, 2020)
The research objective was to describe the application of cooperative learning methods in class XI Science 1 State Senior High School 3 Metro students in improving their short story writing skills. The research method used was observation, documentation, and interviews. Data collection techniques and tools with tests and non-tests. Data analysis included data reduction, data presentation, and drawing conclusions. The results showed an increase in pre-cycle short story writing skills from 198 to cycle I to 262, an increase of 64%. Meanwhile, the average Indonesian learning achievement in pre-cycle got 53 in the first cycle to 69, an increase of 16%. In Cycle II, the score of short story writing skills increased by 32%. As for Cycle III, it increased by 14% with an average learning achievement of 88 or an increase of 9% from the previous cycle. Thus, the cooperative learning method can improve the ability to write short stories in class XI Science 1 State Senior High School 3 Metro odd semester 2017-2018 academic year.